The Master’s Hand - Elena Grigoryeva (Proekt Bajkal, 2015)
The article tells about the master of Irkutsk architecture, S. M. Grigoriev’s collaborative work with young architects in the late 1970s – early 1980s, his tutorial activity and his creative credo.